A strategic initiative to foster interprofessional collaboration: A case report using a men's healthy living programme. Issue 6 (1st November 2016) - Gauthier, Alain P.; Jbilou, Jalila
Abstract: Interprofessional collaboration (IPC) can be challenging, yet it has shown benefits for providers and patients. We examined the existing enablers and barriers to IPC at a local Community Health Center (CHC) and report on the existing types of IPC practice. We also report how implementing a men-sensitive healthy living programme united a team of health professionals/managers in attending to the needs of a population that to date had been largely underserved. A total of 16 employees were interviewed at the CHC. All respondents spoke positively of existing IPC and provided examples of existing collaborative practices. These CHC professionals (clinicians and managers) experienced greater intra- and extra-organisational collaborations as a result of experiencing a community-delivered programme. It also allowed the CHC professionals/managers to rethink the management and structure of collaborative practices and understand the needs and challenges of working with non-traditional partners (men and workplace-based managers). While our findings are context sensitive (case study design), they shed light on how uniting health professionals/managers around a challenging and non-traditional health issue (i.e., improving health in a hard-to-reach population subgroup) can strategically reduce resistance to collaborative practice development by strengthening team cohesion and fostering innovative interactions.